EVALUASI PROGRAM SI-TANTE BERAKSI DALAM UPAYA PENINGKATAN KAPASITAS SDM BERBASIS COACHING KLINIK DI UPTD BAPELKESMAS DINAS KESEHATAN PROVINSI BALI TAHUN 2023 - Sinta Javani; Made Parwati; I Wayan Widiana; I Gede Ratnaya (LPSDI Bina Patria, 2023)
In order to encourage ASN performance improvement, the Regional Government of Bali Province has made various efforts, including conducting ASN performance assessments which have implications for performance allowances, so a breakthrough was designed in the Competency Improvement System (Si-TanTe) with an action plan to form a Coaching Clinic. The data analysis used in this study is qualitative data analysis in the form of coaching clinic activities. The results of this study are the benefits of a competency improvement system (SI TANTE BERAKSI) with a clinical coaching program, which is to help identify the potential of each member, improve work performance, reduce work conflict and improve intrapersonal and interpersonal skills. Intrapersonal ability is the transformation of oneself individually to a better direction. Thus, 'SI TANTE IN ACTION with clinical coaching' becomes very important to improve organizational performance based on improving individual performance. This increase in performance can occur if everyone realizes every potential they have and at the same time knows the deficiencies that still need to be fixed.